A STUDY ON THE STATUS ANALYSIS FOR ESTABLISHMENT OF INTELLIGENT ROAD MANAGEMENT SYSTEM FOR FUTURE ROAD (International Journal of Engineering Sciences & Management Research, 2017)
Domestic road maintenance management systems are not systematic in terms of planning, investigation, efficient budget allocation, and maintenance method selection. Road maintenance budget allocation and priorities are changing according to circumstances. In the road maintenance management system, each facility is not efficiently managed, and management systems such as highways, national highways, provincial roads and municipal roads are maintained differently. Therefore, it is necessary to apply the research, database construction and utilization advancement, budget distribution and decision making advancement from the planning stage to domestic road maintenance management system in depth analysis of the road maintenance management system which is operated effectively in advanced countries. It is believed that this will be an opportunity to enhance the competitiveness of road maintenance system technology internationally by improving the efficiency of domestic road maintenance management system, making budget allocation by scientific method and making optimal decision.